Identifying Price Reviews by Firms: An Econometric Approach - Harris, Mark; Le Bihan, H.; Sevestre, P. (WILEY, 2019)
Price reviews are a potentially costly activity. A significant fraction of unchanged prices may stem from firms not reviewing prices, rather than from obstacles to changing prices per se, such as menu costs. In this paper, we disentangle these two causes of price stickiness by estimating an inflated ordered probit model on a panel of French manufacturing firms. The results point to a low frequency of price reviews, suggestive of the relevance of information costs as a determinant of the observed price stickiness. In view of the “inattentive producers” literature, pointing that the source of price rigidity matters, this is suggestive of a large real effect of monetary policy.